1987
DOI: 10.1093/oxfordjournals.aje.a114717
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and Mortality in the Chicago Western Electric Company Study

Abstract: The relations between coffee consumption and 19-year mortality from all causes, coronary heart disease, and non-coronary causes were assessed in 1,910 white males aged 40-56 years in 1957-1958 from the Chicago Western Electric Company Study. Mortality rates, adjusted for age, serum cholesterol, diastolic blood pressure, and smoking status, were compared for those consuming 0-1, 2-3, 4-5, and 6+ cups of coffee per day; coffee intake, measured at the first anniversary examination, included both caffeinated and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 0 publications
5
36
0
Order By: Relevance
“…These opposite results are in line with the results of a meta-analysis of twenty-one prospective cohort studies (36) . The reason for this sex difference, however, is unknown.…”
Section: Discussionsupporting
confidence: 83%
“…These opposite results are in line with the results of a meta-analysis of twenty-one prospective cohort studies (36) . The reason for this sex difference, however, is unknown.…”
Section: Discussionsupporting
confidence: 83%
“…However, higher con sumption of coffee may adversely affect health in other aspects. For instance, some cohort studies have shown an increased risk of coronary heart disease in heavy coffee drinkers (54)(55)(56), although in others no increase in risk has been found (57)(58)(59). Additionally, the bio logical mechanism behind the inverse association between coffee and the risk of the disease is unknown (37).…”
Section: Discussionmentioning
confidence: 99%
“…Coffee contains caffeine, which has various biological and pharmacological effects 1,2), and the relationships between coffee consumption and cardiovascular disease 3-5), cancer 6,7) and mortality 4,5,[8][9][10][11][12][13][14] have been investigated in the United States and Europe. Green tea contains polyphenols as well as caffeine, and many investigators have examined the potential anticarcinogenic effects of green tea [15][16][17].…”
Section: Introductionmentioning
confidence: 99%